A longitudinal study of the effect of individual and socio-cultural factors on students’ creativity - Park, Hye-sook; Kang, Seokmin; Kim, Sungyeun (Frontiers in Psychology, 2023)
This longitudinal study investigated how characteristics of students, parenting style and attitudes, and teaching methods affect Korean students’ creativity development. Fifth graders (male: 3,623, female: 3,701) from 242 schools in Korea were followed annually from their 5th to 9th grades (indicating from the 5th elementary school grade to 3rd middle school grade in the Korean school system). Exploratory factor analysis, internal consistency reliability (coefficient alpha), and a two-level growth model were performed. After identifying five creativity-related items, exploratory factor analysis revealed one factor. When the measurement invariance assumption was satisfied, we used the mean of the five items as the outcome variable: creativity. We constructed a two-level growth model. Regarding Level 1, we employed peer attachment, self-regulation habits (self-management), parents’ academy-oriented involvement, parent affective support, individualized, interactive teaching methods, and teachers' academic pressure. At Level 2, we used sex and parenting style that were obtained at time point 1. The final combined model incorporating Level 1 and 2 variables showed that the most significant variable affecting the participants’ creativity was self-regulation, followed by peer attachment, parents’ academic support, interaction with parents, teachers’ cognitive support, interaction with teachers, academic pressure from teachers, and relationship with teachers. The methods for enhancing students’ creativity were discussed.